CADMIUM TOXICITY STUDIES AND THE EFFECT OF SEVERAL BIO FEEDS IN Labeo rohita (HAMILTON 1822) - SIVABALAN, V.; ARULDOSS, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The goal of this study was to compare and contrast the contents of proximate analysis, AST, ALT, LDH, and SDH in Labeo rohita gill, muscle, liver, and kidney. It is because of the high nutritional value of this fish as a source of protein in poor nations. The proximate study of L. rohita collected from various locations in Melarungunam, Cudalore district, Tamil Nadu found that hatchery L. rohita had the greatest protein (19.97%) and ash (1.76%) contents, whereas fat (0.84%), carbohydrate (5.39%), and dry matter (24.11%) contents. In the genus Labio rohita. The moisture content of the fish morphology was the greatest (81.42%). Maximum peroxidase and - amylase activity were measured during enzymatic analysis. The liver had the highest concentration of Cd metals, followed by kidney, muscle, and gills, in that order. When compared to other fish, rice bran and tapioca powder treated fish grew the fast.